Reducing Plastic Waste: Utilization of Plastic Bottles as Decorative Plant Containers - Khalimatus Syarivah (Abdimas Paspama, 2024)
Plastic waste is waste that is difficult to decompose and takes tens or even hundreds of years to disintegrate or decompose. The public's lack of concern for the condition of the surrounding environment and lack of understanding of how to process plastic waste properly, results in waste having a negative impact on the environment, including pollution of land, water and air and creating a slum environment. Therefore, plastic bottle waste needs to be recycled into creative products that are attractive and can be useful, such as flower pots or other plants. To reduce the accumulation of plastic bottle waste, we carry out recycling education with the local community and with good management, the negative impact on the environment can be minimized.